PENGARUH KESADARAN WAJIB PAJAK, TARIF PAJAK UMKM DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KANTOR PELAYANAN PAJAK PRATAMA BADUNG UTARA - Ni Kadek Catur Septirani; Komang Krishna Yogantara (Universitas Triatma Mulya, 2020)
Taxpayer compliance is the necessary attitude to support the taxpayer for the orderly observance of taxation regulations. The issues raised in this study are whether taxpayer awareness (X1), MSME tax rate (X2) and tax sanctions (X3) have an effect on MSME (Y) Taxpayer compliance in Tax Office North Badung. The population of this study amounted to 3,350 taxpayer taxpayers who had deposited its income tax in 2018. The study used the Slovin formula which was later sampled in 97. The data analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analyses, hypothesis tests. The results of the analysis showed a regression model Y = 5,064 + 0.211 (X1) + 0.270 (X2) + 0.463 (X3). The conclusion that obtained is a taxpayer awareness (X1) has not partially had an influence on the taxpayer compliance (Y) in Tax Office North Badung which is shown in significance value of 0.072 greater than 0.05. The MSME tax rate (X2) and taxation sanctions (X3) partially have a positive influence on SMSE taxpayer compliance (Y) in Tax Office North Badung, this can be seen in the significance value of 0.000 and 0.019 smaller than 0.05. The magnitude of the influence of taxpayer Awareness (X1), MSME tax rate (X2) and tax sanctions (X3) against MSME taxpayer compliance (Y) in Tax Office North Badung amounted to 69.9% and the remaining 33.1% are influenced by other variables not researched in the study This. The free variables that have a dominant influence on MSME taxpayer compliance can be seen at the value of Standardized Coefficients Beta is a variable of taxation sanctions (X3) of 0.442.